Life of Pi [videorecording (DVD)] - Sharma, Suraj, 1993-; Khan, Irrfan, 1967-2020; Tabu, 1970 November 4-; Spall, Rafe, 1983-; Depardieu, Gérard, 1948-; Martel, Yann (20th Century Fox Home Entertainment, 2013)
A young Pi Patel, overcoming a cataclysmic shipwreck, finds himself stranded on a lifeboat with the last survivor, a ferocious Bengal tiger named Richard Parker.